2020
DOI: 10.1016/j.forpol.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Finnish forest-based companies in transition to the circular bioeconomy - drivers, organizational resources and innovations

Abstract: Forest-based businesses are the center of the transition to the sustainable and competitive circular bioeconomy in Finland. This study explores the transition of Finnish FBS firms to new business models, with a focus on the organizational resources and capabilities needed for transition. It also identifies the important elements in the business environment and the role of innovations in this process. The study uses thematic interviews with managers from various FBS firms and companies from interfacing sectors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 62 publications
3
72
0
1
Order By: Relevance
“…As reaching Future-Fittest involves increased sophistication of, and capacity for, corporate foresight and open innovation, and company culture is the foundation that influences both, culture change is a logical starting point for many companies. This is consistent with the growing literature on bioeconomy transition suggesting that companies should, for example, hire managers, possibly from outside the sector, that can create an encouraging atmosphere, recruit inspiring employees, and aim for more organic company structures (Näyhä 2020a). It is organizational culture that will not only allow, but facilitate efforts toward Future-Fittest.…”
Section: A Path Towards Future-fittest Insights For Industry Managerssupporting
confidence: 85%
See 1 more Smart Citation
“…As reaching Future-Fittest involves increased sophistication of, and capacity for, corporate foresight and open innovation, and company culture is the foundation that influences both, culture change is a logical starting point for many companies. This is consistent with the growing literature on bioeconomy transition suggesting that companies should, for example, hire managers, possibly from outside the sector, that can create an encouraging atmosphere, recruit inspiring employees, and aim for more organic company structures (Näyhä 2020a). It is organizational culture that will not only allow, but facilitate efforts toward Future-Fittest.…”
Section: A Path Towards Future-fittest Insights For Industry Managerssupporting
confidence: 85%
“…Recent work identifies a weakness in forest sector firms due to the collapse of internal research, development, and innovation programs and follow-on loss of expertise where companies often lack employees with the skills and expertise to, "…identify, receive and use state of the art technological and organizational know-how…" (Hayter and Clapp 2020, p. 10). Generally, the literature shows a sector lacking innovation and innovativeness, leading to calls for hiring more innovation-focused management and employees (Näyhä 2020a), as well as training for existing employees that will facilitate a shift towards increased innovativeness (Guererro and Hansen 2020). Ultimately, the path toward Future-Fittest requires a nimble, innovative, and highly-skilled workforce.…”
Section: A Path Towards Future-fittest Insights For Industry Managersmentioning
confidence: 99%
“…The research methodology applied in this study has been described earlier (however, not including details on the backcasting process) in Näyhä (2019Näyhä ( , 2020, because the data for these studies were gathered from the same interviews. The data consist of semi-structured thematic interviews (conducted in spring 2017) with 18 company managers from various FBS firms and companies from interfacing sectors, all of which have operations in Finland.…”
Section: Sample and Approachmentioning
confidence: 99%
“…In order to frame the future states and pathways presented in this study, this section briefly casts a light on respondents' views on the transition and their role as transition actors in general. The issues presented in this section (4.1) have been described and discussed in more detail in earlier publications (see Näyhä 2019Näyhä , 2020.…”
Section: Transition In Finnish Fbs Companies Towards Sustainable and mentioning
confidence: 99%
“…In the theoretical and empirical context, open innovation is interpreted as a differentiating strategy that generates sustained competitiveness for organizations (West et al, 2014). In the study of the relationship between open innovation and Environmental CSR, it has been found that this connection really exists (Silvestre & Ţîrcă, 2019), however, some experts in the field have explained that these two strategic activities have a two-way relationship (Bocquet, Le Bas, Mothe, & Poussing, 2019;Nä yhä , 2019;Wikhamn & Styhre, 2017). Recent studies have shown that products and services developed with internal and external knowledge from open innovation, generate a great deal of benefits for the interest groups of companies, including ecological products, more durable and less deceptive products (not imitations), actions that positively impact the reputation and profits of companies (Ramaanuni & Mukherjee, 2014).…”
Section: Open Innovation Its Effect On Csr Logistics and Performancementioning
confidence: 99%